1998
DOI: 10.1111/j.1440-1746.1998.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined hepatocellular‐cholangiocarcinoma: A clinicopathological study

Abstract: Combined hepatocellular-cholangiocarcinoma (HCC-CC) is an uncommon form of primary liver cancer having features of both hepatocellular and biliary epithelial differentiation. We reviewed 21 cases of this tumour diagnosed between 1972 and 1996 (patient age range 16-79 years; mean patient age 49.7 years; 18 male and three female patients). Histologically, the majority (n = 18) of tumours were 'mixed' tumours, in which areas of hepatocellular and biliary epithelial differentiation were intimately mixed within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
108
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 14 publications
6
108
4
Order By: Relevance
“…In addition, Maeda et al [2] demonstrated that the prognosis of cHCC-CCC, including MHC, is intermediate between that of standard HCC and that of CCC. Only a few studies of MHC have been reported [4,6,7,10]. To date, the clinicopathologic features, appropriate surgical treatment, and outcome of cases of MHC have not been fully clari®ed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Maeda et al [2] demonstrated that the prognosis of cHCC-CCC, including MHC, is intermediate between that of standard HCC and that of CCC. Only a few studies of MHC have been reported [4,6,7,10]. To date, the clinicopathologic features, appropriate surgical treatment, and outcome of cases of MHC have not been fully clari®ed.…”
Section: Introductionmentioning
confidence: 97%
“…Some investigators have suggested that the clinical features of cHCC-CCC, including MHC, resemble those of HCC rather than CCC since most cases of MHC are accompanied by chronic liver disease related to hepatitis due to viral infection, as well as elevated serum levels of alpha-fetoprotein (AFP) [2,4]. In addition, Maeda et al [2] demonstrated that the prognosis of cHCC-CCC, including MHC, is intermediate between that of standard HCC and that of CCC.…”
Section: Introductionmentioning
confidence: 97%
“…Although this entity does demonstrate pathologic features of its well-established biphenotypic counterparts, the characteristics of this neoplasm make diagnosis challenging using conventional radiologic imaging and serologic markers. Moreover, accurate prognostic information is affected by the low frequency of this tumor, which restricts available clinical information even within Original Article A genetic database can be utilized to identify potential biomarkers for biphenotypic hepatocellular carcinoma-cholangiocarcinoma large medical centers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have examined the role of cytoskeletal stability, apoptosis, and the inflammatory cascade in HCC-CC (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Additionally, as HCC-CC poses a diagnostic dilemma for radiologists, tumor specific biomarker may assist in the diagnosis of this neoplasm and prognostic assessment (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…HCC is hepatocyto-origin, and ICC is from the epithelium of the intrahepatic bile duct. CHC is a rare type of liver cancer with features of both hepatocellular and biliary differentiation (1)(2)(3). The pathological structure of CHC is composed of hepatocellular element showing bile production, an intercellular bile canaliculi or trabecular growth pattern and cholangiocellular component showing mucin production or gland formation.…”
Section: Introductionmentioning
confidence: 99%